Long‑term Compressive Strength Properties of Concrete Incorporating Admixtures: Outdoor Exposure Testing in a Coastal Environment - Binna Lee; Jong?Suk Lee; Jae?Suk Ryou (International journal of concrete structures and materials, 2024)
In this study, concrete specimens were fabricated based on domestically manufactured materials, and long-term exposure tests were conducted in a domestic coastal environment. This study analyzes the long-term compressive strength characteristics of concrete mixed with admixtures. The mixed materials used were divided into blast furnace slag and fly ash. The blast furnace slag and fly ash were, respectively, produced by replacing ~ 30% and ~ 15% of the cement. The compressive strength was measured at 28 day, 1 year, and 10 years of age and compared with that of ordinary concrete. In addition, the long-term compressive strength results obtained in this study were compared with those of concrete mixed with admixtures reported in the literature. The strengths of the ordinary specimen at 1 year and 10 years of age increased by ~ 10 MPa and ~ 22 MPa compared with those at 28 day of age. However, concrete mixed with admixtures yielded compressive strength increases of ~ 5 MPa and ~ 26 MPa at 1 year and 10 years of age, respectively, compared with those at 28 day of age. A comparison of the compressive strengths of concrete mixed with admixtures reported in the literature (based on age) and those obtained in this study showed that there was an initial strength difference in the range of 10–25%. However, the compressive strength at 10 years of age was almost similar to those reported in the literature with differences of less than 5%. These findings confirmed that when using pozzolanic admixtures, the development rate of the initial strength may vary owing to various factors; however, the long-term strength converges within a certain range. KCI Citation Count: 0